Effect of Coating and Polishing of Cutting Tool on Machined Surface Quality in Dry Machining of Aluminium Alloy - Dev, Atul; Tandon, Smriti; Kumar, Pankaj; Dutt, Anup (Defence Science Journal, 2020)
Surface quality is one of the major concerns in any machining process. To achieve the higher surface finish, mostly concentrated on machining parameter optimisation. This study has been carried out to study the effect of coating and polishing of flute surface of the solid carbide (WC-Co) endmill cutters on machined surface quality obtained during dry machining of Aluminium alloy 24345WP. Experiments were conducted on Aluminum workpieces with Ø6 mm 2 flute end- mill cutter with and without coating/polishing and their effect on surface quality studied for linear as well as areal surface roughness parameters using white light interferometery. The study concludes that polished flute tool, despite their non-sharp cutting edges, gives considerably better surface finish due to its lowering of chip tool friction. This was also supported by the results obtained from scanning electron microscopy of the cutting tool edge as well as optical microscopy of the obtained machined surface.